Characterization of Nano-Crystalline Carbon from Camphor and Diesel by X-ray Diffraction Technique - Manoj, B. (Asian Journal of Chemistry, 2014)
Hydrocarbons are by far the most widespread precursors among carbon sources employed in the production of carbon nanotubes and carbon nanosphers. In the present study, diesel and camphor have been used as precursors for nanomaterials. Carbonaceous soot produced from combustion of diesel in engine shows the presence of significant amount of carbon nanomaterials. The g band at about 19.28° has been attributed to the presence of amorphous carbon and surface defects in carbon nanotubes. The g band at about 25.81° corresponds to e2g mode of graphite which is related to vibration of sp2 bonded carbon atoms and the presence of ordered carbon nanotubes in diesel soot. The SEM micrographs provide a clear indication that nanoparticle formed in diesel soot are clusters of carbon nanospheres. Energy dispersive spectrum analysis of diesel soot confirms that the soot particles to be composed of primarily carbon and oxygen along with hydrogen. The camphor soot shows g and p bands which reveals the presence of crystalline graphitic carbon. The SEM micrographs of camphor show the presence of carbon nanostructures. It is found nanomaterials formed in the diesel soot consists more of disordered carbon, whereas in camphor it is more of ordered graphite like carbon.